Experimental Measurement of Fiber-Wireless Transmission via Multimode-Locked Solitons From a Ring Laser EDF Cavity - I. S. Amiri; S. E. Alavi; M. R. K. Soltanian; H. Ahmad; N. Fisal; A. S. M. Supa'at (IEEE Photonics Journal, 2015)
This paper describes a demonstration of soliton transmission over fiber-wireless (Fi-Wi) networks using mode-locked stable solitons over a 50-km-long fiber and a short-distance wireless link. Ultrashort optical pulse sources in the 1.5-μm region are seen as increasingly important for achieving ultrahigh-speed optical transmission and signal processing at optical nodes. Mode-locked solitons were generated by a simple ring laser cavity incorporating a very thin layer of carbon nanotube (CNT), together with an erbium-doped fiber (EDF) laser used as an active bulk gain medium. Experimental measurements involved the transmission of the generated mode-locked soliton over a 50-km-long single-mode fiber (SMF), and a radio-frequency (RF) spectrum subsequently generated was a result of beating frequency of wavelengths launched into the photodetector at the other end of the SMF. This RF spectrum array was in the range of WiFi frequencies. System performance was evaluated by first selecting one of the RF carriers centered at 2.5 GHz via an RF bandpass filter and subsequently using this carrier to transmit quadrature phase-shift keying (QPSK) and 16-quadrature amplitude modulation (16-QAM) data signals. The described optical circuit, containing an EDF laser, a CNT, an SMF, and a wireless link, was shown to achieve ultrastable transmission of mode-locked soliton over a long-distance Fi-Wi network.